A novel surgical approach for the management of giant invasive prolactinoma compressing the brainstem. (1st January 2016) - Margari, Niki; Pollock, Jonathan; Stojanovic, Nemanja
Summary: Prolactinomas constitute the largest subsection of all secretory pituitary adenomas. Most are microprolactinomas and are satisfactorily treated by medical management alone. Giant prolactinomas, measuring more than 4 cm in diameter, are rare and usually occur more commonly in men. Macroprolatinomas tend to present with symptoms of mass effect rather than those of hyperprolactinaemia. Dopamine agonists (DA) are the treatment of choice for all prolactinomas. Surgery is usually reserved for DA resistance or if vision is threatened by the mass effects of the tumour. We describe the case of a 52 year-old woman with a giant invasive prolactinoma who required multiple surgical procedures as well as medical management with DA. One of the surgical interventions required a posterior approach via the trans cranial sub occipital transtentorial approach, a surgical technique that has not been previously described in the medical literature for this indication. The giant prolactinoma was reduced significantly with the above approach and patient symptoms from the compressing effects of the tumour were resolved. This case highlights the importance of a multidisciplinary approach to the management of such patients who present with florid neurological sequelae secondary to pressure effects. Although this presentation is uncommon, surgery via a sub occipital transtentorial approach may be considered the treatment of choice in suitable patients with giant invasive prolactinomas compressing the brainstem. Learning points: Giant prolactinomas present with symptoms of mass effect or those of hyperprolactinaemia. Interpretation of the pituitary profile is crucial to guide further investigations and management. Treatment of giant invasive prolactinomas may involve a combination of medical management and multiple surgical interventions. Treatment with DA may cause pituitary haemorrhage or infarction in patients with these tumours. A sub occipital transtetorial approach may be considered the treatment of choice in invasive prolactinomas compressing the brainstem. Multidisciplinary approach of such patients is fundamental for a better outcome.